STOCHASTIC OPTIMISATION OF COFFEE AND DAIRY PRODUCTIONS IN INTEGRATED FARMING SYSTEM IN YOGYAKARTA - Sudantoko, Djoko; Mariyono, Joko (PRESTASI, 2011)
STIE Bank BPD JatengAbstractRisk of profit loss in farming system is inevitable since there is a fluctuation in prices of agricultural products. Diversification is, therefore, the appropriate way to reduce the risk associated with the fluctuation. However, the right combination of production in integrated farming system is very important to consider because it will lead to the high revenue. The objective of this analysis is to assess the levels of production in dairy and coffee farming on whether or not the combination of the productions is optimal. This analysis is based on a study undertaken in Sleman, Yogyakarta, where the integrated farming system exists. The theory of economies of scope is employed in this study, and the combination of productions is tested stochastically. Data are obtained by interviewing 35 producers running dairy and coffee farming simultaneously. The result of this study indicates that the integrated farming system has an advantage in terms of economies of scope, but the combination of products is not optimal. The best alternative to enhance the revenue is to transfer the Robusta coffee production into the fresh milk production, by transferring the resources used in the coffee farming into the dairy farming. Keywords: integrated farming system, stochastic optimisation, product transformation curve